2023
DOI: 10.1109/access.2023.3327620
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Denial of Service Attack Detection for the Internet of Things Using Hybrid Deep Learning Model

Ahmed Ahmim,
Faiz Maazouzi,
Marwa Ahmim
et al.

Abstract: As a result of the widespread adoption of the Internet of Things, there are now hundreds of millions of connected devices, increasing the likelihood that they may be vulnerable to various types of cyberattacks. In recent years, distributed denial of service (DDoS) has emerged as one of the most destructive tools utilized by attackers. Traditional machine learning approaches are typically ineffective and unable to cope with actual traffic properties when used to identify DDoS attacks. This paper introduces a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The approach seeks to identify all DDoS attacks and their subcategories. We found that our model beat other machine learning and deep learning models in terms of true positive rate, accuracy, false alarm rate, average accuracy, and detection rate [15]. Recent years have seen the rise of DDoS as a very disruptive technique for attackers.…”
Section: Literature Surveymentioning
confidence: 65%
“…The approach seeks to identify all DDoS attacks and their subcategories. We found that our model beat other machine learning and deep learning models in terms of true positive rate, accuracy, false alarm rate, average accuracy, and detection rate [15]. Recent years have seen the rise of DDoS as a very disruptive technique for attackers.…”
Section: Literature Surveymentioning
confidence: 65%
“…According to the latest information from Microsoft, there appears to be a threefold increase in DDoS assaults. The notable distributed denial-of-service (DDoS) assaults in 200 were the Amazon Web Services (AWS) attack, the attacks on GitHub DDoS attack, the Dyn DDoS attack that resulted in harm to internet services, and the Mafiaboy strikes [56]. To execute such attacks, hackers utilize several techniques, primarily relying on botnets, to overwhelm the servers of the targeted website or service with a substantial flood of data, overwhelming their ability to process legitimate requests.…”
Section: ) Man-in-the-middle (Mitm) Attackmentioning
confidence: 99%
“…The proposed Optimized Privacy Information Exchange Schema aims to address these vulnerabilities and improve the functionality and performance of the traditional system, with validation from the Scyther tool. The paper [19] presents a deep learning-based intrusion detection system for the IoT environment, specifically targeting DDoS attacks. The proposed model combines different types of deep neural networks to leverage their unique properties and achieve high performance.…”
Section: Related Workmentioning
confidence: 99%